Conjugated Microporous Polymer Nanosheets for Overall Water Splitting Using Visible Light. Issue 38 (18th August 2017) - Wang, Lei; Wan, Yangyang; Ding, Yanjun; Wu, Sikai; Zhang, Ying; Zhang, Xinlei; Zhang, Guoqing; Xiong, Yujie; Wu, Xiaojun; Yang, Jinlong; Xu, Hangxun
Abstract : Direct water splitting into H2 and O2 using photocatalysts by harnessing sunlight is very appealing to produce storable chemical fuels. Conjugated polymers, which have tunable molecular structures and optoelectronic properties, are promising alternatives to inorganic semiconductors for water splitting. Unfortunately, conjugated polymers that are able to efficiently split pure water under visible light (400 nm) via a four‐electron pathway have not been previously reported. This study demonstrates that 1, 3‐diyne‐linked conjugated microporous polymer nanosheets (CMPNs) prepared by oxidative coupling of terminal alkynes such as 1, 3, 5‐tris‐(4‐ethynylphenyl)‐benzene (TEPB) and 1, 3, 5‐triethynylbenzene (TEB) can act as highly efficient photocatalysts for splitting pure water (pH ≈ 7) into stoichiometric amounts of H2 and O2 under visible light. The apparent quantum efficiencies at 420 nm are 10.3% and 7.6% for CMPNs synthesized from TEPB and TEB, respectively; the measured solar‐to‐hydrogen conversion efficiency using the full solar spectrum can reach 0.6%, surpassing photosynthetic plants in converting solar energy to biomass (globally average ≈0.10%). First‐principles calculations reveal that photocatalytic H2 and O2 evolution reactions are energetically feasible for CMPNs under visible light irradiation. The findings suggest that organic polymers hold great potential for stable and scalable solar‐fuel generation. Abstract : Polymer nanosheets for photocatalytic overall water splitting : 1, 3‐diyne‐linked conjugated microporous polymer nanosheets can act as highly efficient photocatalysts for splitting pure water (pH ≈ 7) into stoichiometric amounts of H2 and O2 using visible light. This findings suggest that organic polymers hold great potential for stable and scalable solar‐fuel generation using sunlight as the only energy input.